Nine Forward–Backward Translations of the Hopkins Symptom Checklist-25 With Cultural Checks - Nabbe, Patrice; Le Reste, Jean Yves; Guillou-Landreat, Morgane; Assenova, Radost; Kasuba Lazic, Djurdjica; Czachowski, Slawomir; Stojanović-Špehar, Stanislava; Hasanagic, Melida; Lingner, Heidrun; Clavería, Ana; Rodríguez-Barragán, María; Sowinska, Agnieszka; et al. (Frontiers in Psychiatry, 2021)
Background: The Hopkins Symptom Checklist-25 (HSCL-25) is an effective, reliable and ergonomic tool that can be used for depression diagnosis and monitoring in daily practice. To allow its broad use by family practice physicians (FPs), it was translated from English into nine European languages (Greek, Polish, Bulgarian, Croatian, Catalan, Galician, Spanish, Italian, and French) and the translation homogeneity was confirmed. This study describes this process. Method: First, two translators (an academic translator and an FP researcher) were recruited for the forward translation (FT). A panel of English-speaking FPs that included at least 15 experts (researchers, teachers and practitioners) was organized in each country to finalize the FT using a Delphi procedure. Results: One or two Delphi procedure rounds were sufficient for each translation. Then, a different translator, who did not know the original version of the HSCL-25, performed a backward translation in English. An expert panel of linguists compared the two English versions. Differences were listed and a multicultural consensus group determined whether they were due to linguistic problems or to cultural differences. All versions underwent cultural check. Conclusion: All nine translations were finalized without altering the original meaning.